Nobiliss. Virginis Annri'Schurman, Opuscula Hebr{u1B20}Gr{u386C} Latina, Gallica : Prosaica & metrica - Schurman, Anna Maria van, 1607-1678 ([Netherlands] : Elsevier, 2014)
Anna Maria Van Schurman (1607-1678) is perhaps the only female author in the Elzeviers' catalogue. She was born in Germany, but moved to Utrecht in the Netherlands at a young age. As a child genius, she could already read at the age of 4. In her teenage years, she excelled in Latin and other subjects, as well as traditionally female pastimes, such as paper cutting, painting, and embroidery. At a time when women were not allowed into higher education, she became the first female student in the Netherlands at Utrecht University from 1636. This book is a collection of her poetry in various languages, as well as her Latin- and French-language letters to respected scholars of her time, demonstrating her important position in seventeenth century intellectual life.
'First published by Abraham and Bonaventura Elzevier in 1648. Republished by Elsevier B.V. in 2014.'
Contains texts in Latin, French, Greek and Hebrew.
Elsevier
Keywords: Schurman, Anna Maria van, -- 1607-1678 -- Correspondence; Schurman, Anna Maria van, -- 1607-1678.; Poetry; Women -- Education -- Netherlands -- Early works to 1800.; Poetry; Women -- Education; Netherlands; Electronic books; Early works; Records and correspondence